PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SMK PLUS PRATAMA ADI BANDUNG - Johni S. Pasaribu (Universitas Widyatama, 2021)
The rapid development of the computer world that brings every individual or group of people will use information and communication technology in every activity. Likewise in the world of education, including libraries that utilize information and communication technology in managing the process of borrowing and returning library books. The benefits of making a web-based library information system include being able to save time where there is no need for manual recording, making it easier to find book data or library members, making it easier in making book loan reports and other reports and other benefits. The research method used is Research and Development (R&D). The making of software is done by a waterfall model consisting of: (1) needs analysis, (2) design, (3) implementation, and (4) testing. Then UML visual modeling is used which is the standardization of modeling language for object-oriented software development. The expected results of this study produce a web-based library information system using the YII Framework with MVC (Model View Controller) method in SMK Plus Pratama Adi Bandung that can solve existing problems. The formulation of the problem of this research is how to build a library information system in SMK Plus Pratama Adi Bandung so that it can present accurate and efficient information. The purpose of this research is to produce a library information system.